2001
DOI: 10.1097/00000478-200110000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Complete Hydatidiform Mole From Its Mimics by Immunohistochemistry of the Paternally Imprinted Gene Product p57 KIP2

Abstract: The p57KIP2 protein is a cell cycle inhibitor and tumor suppressor encoded by a strongly paternally imprinted gene. We explored the utility of p57KIP2 as a diagnostic marker in hydatidiform mole, a disease likely the result of abnormal dosage and consequent misexpression of imprinted genes. Using a monoclonal antibody on paraffin-embedded, formalin-fixed tissue sections, the authors evaluated p57KIP2 expression in normal placenta and in 149 gestations including 59 complete hydatidiform moles, 39 PHMs, and 51 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
126
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(137 citation statements)
references
References 20 publications
7
126
1
3
Order By: Relevance
“…However, previous studies have demonstrated that diagnosis of hydatidiform moles based on morphology alone, even by experienced pathologists with specialized training, is subject to interobserver variability and therefore suboptimal diagnostic reproducibility. [9][10][11][12][13][14][15] A number of studies have demonstrated the value of ancillary techniques, including immunohistochemical analysis of cyclin-dependent kinase inhibitor 1C (CDKN1C/p57/Kip2, the protein product of the CDKN1C imprinted gene located at chromosome 11p15.5; referred to henceforth as p57) expression [16][17][18][19][20][21][22][23][24][25][26][27] and molecular genotyping via PCR amplification of short tandem repeat loci, 23,25,[28][29][30][31] for improving the diagnosis of hydatidiform moles. Genotyping is particularly valuable because it allows for specific distinction of complete hydatidiform moles, partial hydatidiform moles, and nonmolar specimens from one another due to their unique genetics.…”
mentioning
confidence: 99%
“…However, previous studies have demonstrated that diagnosis of hydatidiform moles based on morphology alone, even by experienced pathologists with specialized training, is subject to interobserver variability and therefore suboptimal diagnostic reproducibility. [9][10][11][12][13][14][15] A number of studies have demonstrated the value of ancillary techniques, including immunohistochemical analysis of cyclin-dependent kinase inhibitor 1C (CDKN1C/p57/Kip2, the protein product of the CDKN1C imprinted gene located at chromosome 11p15.5; referred to henceforth as p57) expression [16][17][18][19][20][21][22][23][24][25][26][27] and molecular genotyping via PCR amplification of short tandem repeat loci, 23,25,[28][29][30][31] for improving the diagnosis of hydatidiform moles. Genotyping is particularly valuable because it allows for specific distinction of complete hydatidiform moles, partial hydatidiform moles, and nonmolar specimens from one another due to their unique genetics.…”
mentioning
confidence: 99%
“…7,35,36 In addition to histopathology, we used the negativity of p57 KIP2 immunostaining as a specific tool for the diagnosis of CHM. 4,5 In our study, molecular tests for the DNA content in PHM were not available to confirm the triploidy of the mutated cases. However, histologic criteria, positivity of p57 KIP2 immunostaining, and high levels of b-hCG, taken together, were arguments in favor of the diagnosis of PHM and for exclusion of the diagnosis 26 who demonstrated that NLRP7 mutations or variants are responsible not only for diploid biparental moles as previously shown, but also for diploid androgenetic moles, triploid moles, and for tetraploid spontaneous abortions.…”
Section: Commentmentioning
confidence: 82%
“…3 With the availability of p57 KIP2 immunostaining (the product of a strongly paternally imprinted and maternally expressed gene), it may be possible to classify objectively these lesions. 4,5 P57 KIP2 immunostaining is absent in CHM because it lacks a maternal genome, whereas PHM and spontaneous abortion show positive staining. 4,5 Molecular techniques using the DNA content differences are needed to distinguish between triploid PHM and diploid spontaneous abortion in some challenging cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of hypoxia on expression of 11p15.5 genes in primary term human trophoblasts. Cells were cultured for 24 h, 48 h or 72 h in either hypoxia or standard conditions as described in Section 2, and transcript levels were determined by qRT-PCR using four different placentas as described in mole [17,46]. In murine trophoblast giant cells p57…”
Section: Discussionmentioning
confidence: 99%